Тема козаччини у творчості Проспера Меріме - Марченко, Тетяна Михайлівна; Marchenko, Tetiana (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті йдеться про період козаччини в історії українського народу та оцінку його західноєвропейськими митцями. Боротьба за свою незалежність – наскрізна тема українського народу у всі часи. Велику увагу приділено розгляду очільників козаків, зокрема Івана Мазепи та Богдана Хмельницького. Постать гетьмана Богдана Хмельницького у творчості Проспера Меріме – одна зі знакових, яка представляє всю козаччину. Змалювання образу українського керманича у творах французького письменника надзвичайно патетичне, велемовне, позитивне. The essay is focused on a period of Cossacks’ movement in the history of Ukrainian nation as well as on its assessment by the Western-European artists. The struggle of Ukrainian people for their independence has always been a prominent issue. In the foreground of the research is the role of the Cossacks’ leaders, such as Ivan Mazepa and Bogdan Khmelnitsky. The figure of a unique Ukrainian hetman Bogdan Khmelnitsky in Prosper Merimee’s literary legacy is fairly symptomatic: this outstanding warrior exemplifies the entire Cossacks’ movement. The portrayal of the Ukrainian people’s helmsman in the novels of the French writer is extremely emotional, positive and eloquent.
The Theme of Cossacks’ Movement in Prosper Merimee’s Novels
Keywords: незалежність; козаччина; гетьман; Богдан Хмельницький; Іван Мазепа; independence; Cossacks’ movement; hetman; Bogdan Khmelnitsky; Ivan Mazepa